2016
DOI: 10.15406/aovs.2016.05.00160
|View full text |Cite
|
Sign up to set email alerts
|

Can Foveal Avascular Zone (FAZ) Assessment By OCT Angiography, Used For Grading Of Diabetic Retinopathy?

Abstract: OpinionDiabetic retinopathy (DR) not only is common among diabetics, but also is leading cause of new onset blindness in developed countries. Fortunately, visual loss is preventable by early detection and treatment of DR. Current screening guidelines suggest yearly to monthly full dilated fundus exam by ophthalmologist, based on DR grade. The World Health Organization (WHO) estimated that the number of individuals with diabetes mellitus (DM) to rise to 360 million by the year 2030 [1]. This number of affected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Adding quantitative values including FAZ size to the current grading system may improve DR scaling system to a more trackable clinically applicable scaling. [ 109 110 111 ]…”
Section: Discussionmentioning
confidence: 99%
“…Adding quantitative values including FAZ size to the current grading system may improve DR scaling system to a more trackable clinically applicable scaling. [ 109 110 111 ]…”
Section: Discussionmentioning
confidence: 99%
“…[21] OCTA believed to be more accurate than FFA to demarcate and measure the FAZ, as it is not obscured by leakages, pooling or staining from fluorescein. [22] On the other hand, data in the literature regarding the FAZ area in diabetic patients without DR are conflicting. Kim et al and some other research groups reported a noted enlargement of the FAZ in NDR group in comparison with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…One of the promising features of this technology is that beside qualitative data, it provides quantitative data regarding retinal and choroidal structural and vascular indices like Vascular Density (VD), Foveal Avascular Zone (FAZ), etc. Feasible Quantitative data provided by OCTA; may revolutionize current ophthalmic practice in regards of predicting [2,3], grading [4,5], following up treatment in patients with important vascular diseases like diabetic retinopathy, retinal vein obstruction, choroidal neovascularization, etc. [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Then, these data could be used for everyday clinical practices. For an instance, quantitative assessment of Foveal Avascular Zone (FAZ) could be useful in optimal selection of therapy in patients with Diabetic Macular Edema (DME) [11] or even grading the severity of Diabetic Retinopathy (DR) [5,12]. It has also shown that FAZ metrics could change in response to treatment [6] so it could be used in following up patients.…”
Section: Introductionmentioning
confidence: 99%